Theranostic applications of phage display to control leishmaniasis: selection of biomarkers for serodiagnostics, vaccination, and immunotherapy - Coelho,Eduardo Antonio Ferraz (2015)
AbstractPhage display is a high-throughput subtractive proteomic technology used for the generation and screening of large peptide and antibody libraries. It is based on the selection of phage-fused surface-exposed peptides that recognize specific ligands and demonstrate desired functionality for diagnostic and therapeutic purposes. Phage display has provided unmatched tools for controlling viral, bacterial, fungal, and parasitic infections, and allowed identification of new therapeutic targets to treat cancer, metabolic diseases, and other chronic conditions. This review presents recent advancements in serodiagnostics and prevention of leishmaniasis -an important tropical parasitic disease- achieved using phage display for the identification of novel antigens with improved sensitivity and specificity. Our focus is on theranostics of visceral leishmaniasis with the aim to develop biomarker candidates exhibiting both diagnostic and therapeutic potential to fight this important, yet neglected, tropical disease.